2021
DOI: 10.1111/evo.14185
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic divergence and demographic history shed light on island‐mainland population dynamics and melanic plumage evolution in the white‐winged Fairywren*

Abstract: The existence of distinct traits in island versus mainland populations offers opportunities to gain insights into how eco‐evolutionary processes operate under natural conditions. We used two island colonization events in the white‐winged fairywren (Malurus leucopterus) to investigate the genomic and demographic origin of melanic plumage. This avian species is distributed across most of Australia, and males of the mainland subspecies (M. l. leuconotus) exhibit a blue nuptial plumage in contrast to males of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 78 publications
5
33
0
Order By: Relevance
“…Our phylogenomic and population genomic analysis indicate that the divergence of White-shouldered Fairywren populations throughout New Guinea occurred within approximately the last 800,000 years. Reduced genetic diversity in black and pied populations, relative to the brown population, indicates that each population may have experienced a bottleneck following this expansion, which highlights the poor dispersal capabilities of fairywrens (Rowley and Russell 1997;Walsh et al 2021) and the strength of lowland biogeographic barriers in New Guinea (Marki et al 2018). All immediate relatives among Malurus fairywrens, including the sister species M. melanocephalus, are characterized by cryptic brown plumage in females, and our phylogenetic reconstruction is consistent with the ancestral females of extant White-shouldered Fairywren populations lacking ornamentation and a single evolutionary origin of black and pied female ornamentation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our phylogenomic and population genomic analysis indicate that the divergence of White-shouldered Fairywren populations throughout New Guinea occurred within approximately the last 800,000 years. Reduced genetic diversity in black and pied populations, relative to the brown population, indicates that each population may have experienced a bottleneck following this expansion, which highlights the poor dispersal capabilities of fairywrens (Rowley and Russell 1997;Walsh et al 2021) and the strength of lowland biogeographic barriers in New Guinea (Marki et al 2018). All immediate relatives among Malurus fairywrens, including the sister species M. melanocephalus, are characterized by cryptic brown plumage in females, and our phylogenetic reconstruction is consistent with the ancestral females of extant White-shouldered Fairywren populations lacking ornamentation and a single evolutionary origin of black and pied female ornamentation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced genetic diversity in black and pied populations, relative to the brown population, indicates that each population may have experienced a bottleneck following this expansion, which highlights the poor dispersal capabilities of fairywrens (Rowley and Russell 1997; Walsh et al. 2021) and the strength of lowland biogeographic barriers in New Guinea (Marki et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Walsh et al. (2021) take advantage of the mainland and island populations of white‐winged fairywrens ( Malurus leucopterus ) to study the evolution of plumage traits. This species can be found across most of Australia and has been classified into several subspecies.…”
Section: Figurementioning
confidence: 99%
“…Using genomic and demographic analyses, Walsh et al. (2021) revealed that the divergence between the mainland population and the Dirk Hartog Island population was more recent (ca. 173,000 generations ago) than the divergence between the mainland population and Barrow Island population (about 1.75 million generations ago).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation